Supply Chain Management Control of Fish Canning Industry in Morocco - Hamri, Mohammed Hicham; Rharoubi, Ilham (European Scientific Journal, ESJ, 2018)
Management control is increasingly adapted to the changes taking place at inter-firm level of business exchanges. By taking the form of an interorganizational control, the latter aims to reduce uncertainty, avoid opportunism and seek to make the most of an exchange relationship between two organizations. This article analyses some of the main studies dealing with inter-organizational control in the context of supply chain. We present literature review on this type of control, its typology and its approaches and theories. Thanks to its marine biological heritage, Morocco is a world exporter of sea products. The fish preserve sector occupies an important place in the Moroccan economy with a large turnover. This paper presents an exploratory study of this sector where we try to explain the functioning within the canneries of the Souss Massa region in terms of logistic management, the management control function, the management of transport and costs and finally the performance management methods. Based on 12 interviews with managers of canneries in the region, the results of this exploratory study will form the basis on which we will base our main study.